Lymphoma risk in systemic lupus: effects of disease activity versus treatment. Issue 1 (8th January 2013) - Bernatsky, Sasha; Ramsey-Goldman, Rosalind; Joseph, Lawrence; Boivin, Jean-Francois; Costenbader, Karen H; Urowitz, Murray B; Gladman, Dafna D; Fortin, Paul R; Nived, Ola; Petri, Michelle A; Jacobsen, Soren; Manzi, Susan; et al.
Abstract : Objective: To examine disease activity versus treatment as lymphoma risk factors in systemic lupus erythematosus (SLE). Methods: We performed case–cohort analyses within a multisite SLE cohort. Cancers were ascertained by regional registry linkages. Adjusted HRs for lymphoma were generated in regression models, for time-dependent exposures to immunomodulators (cyclophosphamide, azathioprine, methotrexate, mycophenolate, antimalarial drugs, glucocorticoids) demographics, calendar year, Sjogren's syndrome, SLE duration and disease activity. We used adjusted mean SLE Disease Activity Index scores (SLEDAI-2K) over time, and drugs were treated both categorically (ever/never) and as estimated cumulative doses. Results: We studied 75 patients with lymphoma (72 non-Hodgkin, three Hodgkin) and 4961 cancer-free controls. Most lymphomas were of B-cell origin. As is seen in the general population, lymphoma risk in SLE was higher in male than female patients and increased with age. Lymphomas occurred a mean of 12.4 years (median 10.9) after SLE diagnosis. Unadjusted and adjusted analyses failed to show a clear association of disease activity with lymphoma risk. There was a suggestion of greater exposure to cyclophosphamide and to higher cumulative steroids in lymphoma cases than the cancer-free controls. Conclusions: In this large SLE sample, there was a suggestion of higher lymphoma risk with exposure to cyclophosphamide and high cumulative steroids. Disease activity itself was not clearly associated with lymphoma risk. Further work will focus on genetic profiles that might interact with medication exposure to influence lymphoma risk in SLE.